IMPLEMENTATION OF GUIDED INQURY LABORATORY WORKSHEET TO IMPROVE PROBLEM SOLVING SKILL - SHABRINA SAFITRI, NUR; , MADLAZIM (Inovasi Pendidikan Fisika, 2018)
One of the way to improve students science competence is by applying inqury learning. Alternative levels of inquiry that can be applied into classroom is guided inquiry laboratory. Laboratory activity can improve process skill, scientific thinking, and problem solving. This research was conducted with aim to describe the validity and effectivity of guided inquiry laboratory worksheet in term of global warming material to improve problem solving skill. Before worksheet was implemented, the worksheet must be scored by validator. The worksheet is valid, if validator give good score in term of content and construct validity items. Worksheet is effective when the n-gain score greater than 0.3 and students giving a good respons after worked their worksheet. This research is development research by using ADDIE model. The result of worksheet validation by two validator is very valid and it can be used in implementation phase. Worksheet was implemented to 31 student grade XI in SMA Negeri 1 Taman, Sidoarjo to know the effectivity. Pre-test and post-test score were obtained in implementation phase. Students performance was good while doing post-test. Students can reach every problem solving skill indicator after they worked on their worksheet. The average of student n-gain score is 0.77 and it categorized in high category. This result show that there was an improvement in student problem solving skill. Student response questionnaire was distributed at the end of learning process. Student response to worksheet shows the excecllent result. So, the guided inqury laboratory student worksheet to improve problem solving skill is effective. Keywords: guided inquiry laboratory, worksheet, problem solving skill.